2018 IEEE Globecom Workshops (GC Wkshps) 2018
DOI: 10.1109/glocomw.2018.8644110
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Wireless QoS Analysis for Real-Time Control in URLLC

Abstract: One of the major goals of ultra-reliable and lowlatency communication (URLLC) is to enable real-time wireless control systems. However, it is challenging to use URLLC throughout the control process since a huge amount of wireless resource is needed to maintain the rigorous quality-of-service (QoS) in URLLC, i.e, ultra reliability and low latency. In this paper, our goal is to discuss that whether the extreme high QoS in URLLC leads to better control performance than low QoS during the control process. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…However, various attempts to overcome its vulnerability are needed, since wireless networks are relatively insecure compared to wired networks. As the MQTT protocol supports QoS, the optimal QoS for real-time communication can be set [ 23 ]. In addition, while using the MQTT, a standby database can be placed between the gateway and the server [ 24 ], and the current protocol can be upgraded or attached parallel to other wireless communication protocols to address network failures [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, various attempts to overcome its vulnerability are needed, since wireless networks are relatively insecure compared to wired networks. As the MQTT protocol supports QoS, the optimal QoS for real-time communication can be set [ 23 ]. In addition, while using the MQTT, a standby database can be placed between the gateway and the server [ 24 ], and the current protocol can be upgraded or attached parallel to other wireless communication protocols to address network failures [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each node can access both cellular channels (in which the node is the PU) and cognitive channels (in which the node is the SU). D2D enables direct communication between two nodes without traversing the base station (BS), particularly the macrocell (MC) BS (or a central controller) that has the largest coverage in 5G networks [5] using D2D communication, a node can access both cellular and cognitive channels; as a result, it improves spectrum efficiency and QoS [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, our motivation is to obtain a communicationcontrol co-design scheme to reduce the usage of the extremely high QoS in URLLC, where we intend to use dynamic QoS allocation, i.e., both extremely high QoS and relatively low QoS, to serve the control process. In [20] and [21], we have shown that the hybrid high and low communication QoS can be adopted in wireless control systems. In this paper, we further discuss our dynamic QoS allocation method by communication-control co-design in details.…”
Section: Introductionmentioning
confidence: 99%